Characterization of Reduced-Fat Mayonnaise and Comparison of Sensory Perception, Rheological, Tribological, and Textural Analyses - Schädle, Christopher; Bader-Mittermaier, Stephanie; Sanahuja, Solange (Foods, 2022)
Reduced-fat products can help to fight obesity and its associated health risks. To de-velop appealing products, both product-specific fat replacers and suitable analytical methods for the characterization of fat-associated properties are important. The rheology, tribology, texture, and spreadability of a reduced-fat mayonnaise with different concentrations of corn dextrin were analyzed to determine properties such as flow behavior, viscosity, lubricity, firmness, and stickiness. Addition-ally, a sensory panel analyzed the samples for their mouthfeel (creaminess, firmness, and stickiness). Correlations between the results of the instrumental methods suggested that the analytical effort for the future development of appealing reduced-fat food products can be reduced. In addition, several correlations were identified between the instrumental and the sensory data. Results from tribological measurements correlated with the sensory attribute of stickiness, suggesting that tribometry can complement or constitute an alternative to complex and expensive human sensory tests. Additionally, the use of Stevens’ power law showed a high correlation between the Kokini oral shear stress and the sensory attribute of creaminess. The instrumental texture properties (firmness, stickiness) also correlated with the sensory sensation. The identified correlations obtained from comparing different methods may help to estimate the possible applications of new fat replacers and facilitate innovative product development.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Calorie-reduced; Corn dextrin; Dietary fiber; Emulsion; Lubricity; Rheology; Spreadability; Tribology; Viscosity

Influence of Fat Replacers on the Rheological, Tribological, and Aroma Release Properties of Reduced-Fat Emulsions - Schädle, Christopher; Sanahuja, Solange; Bader-Mittermaier, Stephanie (Foods, 2022)
Reduced-fat food products can help manage diet-related health issues, but consumers of-ten link them with poor sensory qualities. Thus, high-quality fat replacers are necessary to develop appealing reduced-fat products. A full-fat model emulsion was reduced in fat by replacing fat with either water, lactose, corn dextrin (CD), inulin, polydextrose, or microparticulated whey protein (MWP) as fat replacers. The effect of fat reduction and replacement, as well as the suitability of different types of fat replacers, were determined by analyzing fat droplet size distribution, composition, rheological and tribological properties, and the dynamic aroma release of six aroma compounds prevalent in cheese and other dairy products. None of the formulations revealed a considerable effect on droplet size distribution. MWP strongly increased the Kokini oral shear stress and viscosity, while CD exhibited similar values to the full-fat emulsion. All four fat replacers improved the lubricity of the reduced-fat samples. Butane-2,3-dione and 3-methylbutanoic acid were less affected by the changes in the formulation than butanoic acid, heptan-2-one, ethyl butanoate, and nonan-2-one. The aroma releases of the emulsions comprising MWP and CD were most similar to that of the full-fat emulsion. Therefore, CD was identified as a promising fat replacer for reducedfat emulsions.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Cheese aroma; Corn dextrin; Dietary fiber; Inulin; Lubricity; Microparticulated whey protein; Nutriose; Polydextrose; Proton-transfer-reaction mass spectrometry (PTR-MS); Simplesse

The combined effects of different fat replacers and rennet casein on the properties of reduced-fat processed cheese - Schädle, Christopher; Eisner, Peter; Bader-Mittermaier, Stephanie (Journal of Dairy Science, 2020)
Reduced-fat food products can help to prevent obesity and other diet-related diseases. However, the removal of fat often impairs the sensory and textural properties of foods, leading to low consumer acceptance. In this study, we tested various concentrations of fat replacers (inulin, corn dextrin, polydextrose, and microparticulated whey protein) combined with rennet casein to investigate their effects on the melting behavior, dynamic rheological properties, and hardness of reduced-fat processed cheese. We found that increasing concentrations of inulin and corn dextrin reduced the flowability of cheese in the melting test and can thus be used to inhibit flow during heating. Microparticulated whey protein did not affect flowability but caused an increase in the storage and loss moduli as well as the temperature at gel-sol transition. A similar effect was also shown for rennet casein, whereas inulin and polydextrose had little or no effect on these rheological parameters. Corn dextrin had no effect on the storage and loss moduli, but affected the gel-sol transition temperature. No changes in hardness were detected for any concentration of the fat replacers, but increasing the rennet casein content also increased the hardness of the samples, regardless of the fat replacer used. Our results indicate the different concentrations and combinations of fat replacers and rennet casein that can be included in reduced-fat processed cheese to develop products with specific rheological properties, thus meeting future demand for reduced-fat products with attractive sensory attributes.
CRIS-Team Scopus Importer:2020-03-20
Keywords: calorie reduction; flowability; hardness; rheology

The Effect of Corn Dextrin on the Rheological, Tribological, and Aroma Release Properties of a Reduced-Fat Model of Processed Cheese Spread - Schädle, Christopher; Bader-Mittermaier, Stephanie; Sanahuja, Solange (Molecules, 2022)
Low-calorie and low-fat foods have been introduced to the market to fight the increasing incidence of overweightness and obesity. New approaches and high-quality fat replacers may overcome the poor organoleptic properties of such products. A model of processed cheese spread (PCS) was produced as a full-fat version and with three levels of fat reduction (30%, 50%, and 70%). Fat was replaced by water or by corn dextrin (CD), a dietary fiber. Additionally, in the 50% reduced-fat spreads, fat was replaced by various ratios of CD and lactose (100:0, 75:25, 50:50, 25:75, and 0:100). The effect of each formulation was determined by measuring the textural (firmness, stickiness, and spreadability), rheological (flow behavior and oscillating rheology), tribological, and microstructural (cryo-SEM) properties of the samples, as well as the dynamic aroma release of six aroma compounds typically found in cheese. Winter’s critical gel theory was a good approach to characterizing PCS with less instrumental effort and costs: the gel strength and interaction factors correlated very well with the spreadability and lubrication properties of the spreads. CD and fat exhibited similar interaction capacities with the aroma compounds, resulting in a similar release pattern. Overall, the properties of the sample with 50% fat replaced by CD were most similar to those of the full-fat sample. Thus, CD is a promising fat replacer in PCS and, most likely, in other dairy-based emulsions.
CRIS-Team Scopus Importer:2022-04-08
Keywords: cheese aroma; dietary fiber; flavor release; lubrication; proton-transfer-reaction mass spectrometry (PTR-MS); rheology; structure; texture; tribology; viscosity